From Classroom to Screen: Students’ Preferences for Online TOEFL Learning - Zakiyah, Zakiyah; Ulfa, Nurina; Amanah, Firma Pradesta (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2024)
Online learning has become essential for continuing education, and the TOEFL exam, a subject well-suited for virtual instruction, has seamlessly transitioned to online platforms to facilitate uninterrupted learning. This research investigates students’ preferences for virtual TOEFL instruction and the challenges encountered during online classes. It surveyed 83 students from four faculties at UIN Raden Intan Lampung, using questionnaires and interviews to collect data. Results showed mixed views on TOEFL learning methods: while some students preferred online over offline learning, others were ambivalent. Almost half (49.4%) were neutral on whether online learning improves focus, while 31.1% had mixed views, with 15.7% agreeing and 15.4% disagreeing. These varied perspectives underscore the complexity of learning preferences and the need for tailored language acquisition strategies. Interviews further indicated a preference for offline learning, primarily due to issues with internet connectivity and home distractions affecting TOEFL comprehension.